The SPB-Box Transcription Factor AaSPL2 Positively Regulates Artemisinin Biosynthesis in Artemisia annua L. - Lv, Zongyou; Wang, Yun; Liu, Yan; Peng, Bowen; Zhang, Lei; Tang, Kexuan; Chen, Wansheng (Frontiers in Plant Science, 2019)
Artemisinin, an important compound produced by Artemisia annua, is the active ingredient in the treatment of malaria. Jasmonic acid, one of the phytohormones, is an important elicitor of artemisinin biosynthesis by enhancing transcription levels of transcription factors. SPL transcription factors are plant-specific transcription factors of plant growth, development, and secondary metabolism regulation. However, to date, the SPL transcription factors that regulate artemisinin biosynthesis is currently unclear. Here, we show that an SPL transcription factor can positively regulate artemisinin biosynthesis by binding to the promoter of artemisinin biosynthetic pathway genes. We screened AaSPL2 by gene expression profiles analysis in 14 SPL transcription factors. We demonstrated that AaSPL2 can activate the promoter of DBR2 by dual-LUC assy. Moreover, in the AaSPL2 overexpression plants, the artemisinin content was increased by 33-86%, and in the AaSPL2 -RNAi transgenic plants, artemisinin content was decreased by 33-65%. These data suggest that AaSPL2 and DBR2 interact with a “GTAC” cis-element in the DBR2 promoter, mediating the transcriptional activation of DBR2 in response to JA and resulting in the improvement on artemisinin content.